ORGANISASI PEMERINTAH DAERAH: MEWUJUDKAN TATA PAMONG YANG BAIK (GOOD GOVERNANCE) - Darmanto (Jurnal Organisasi dan Manajemen, 2006)
The application of Government Regulation Number 22 /1999 on local government has an important effect on the development of local government. Local government has more autonomy and larger opportunities to develop their region. However, the application of local autonomy will be meaningless if local government does not improve their performance. As an organization, local government has a bureaucracy culture. Generally, bureaucracy culture has not support the aim of the local government. Bureaucracy still has a problem that should be solved right away, among others are: personal performance, payment system, and ethics. Public service is another aspect which should be improved. Local autonomy regulation will be effective if local government can improve the public administrator function.